Pengaruh Model Pembelajaran Inquiry Terhadap Hasil Belajar Siswa Pada Materi Pencemaran Lingkungan di SMA Swasta PAB 8 Saentis - Lubis, Baby Arlita; Manurung, Binari; Harahap, Fauziyah (Jurnal Pendidikan Biologi, 2016)
This study aims to determine the effect of inquiry based learning modelon studentsâlearning outcome of the environmental pollutiontopic at SMA Swasta PAB 8 Saentis. The research method used is quasi experimentwith sample as much as 3 classes, those are takenby using the technic of cluster random sampling.Guided inquiry based learning model is taught in class X2, modified free inquiry based learning modelis taughtin classX5, and traditional based learning model is taughtin class X3. The instrument is used in this study islearning outcome test in form multiple choice. The techniqueof data analysis used in this study isanalysis covariatbyusingthe program of SPSS 21.0 for Windows. The study result showed that there was effect ofinquiry based learning modelon studentsâ learning outcome (F=6.58 ; P=0.002). Studentsâ learning outcome that were taught by guided inquiry based learning model(73.36Â±11.443) was highestthanmodified free inquiry based learning model(67.27Â±12.050) was higherthan traditional based learning model (64.00Â±13.561).